ASSESSMENT OF ADVERSE DRUG REACTIONS OCCURRING AT DEPARTMENT OF NEUROLOGY OF A TERTIARY CARE HOSPITAL IN INDIA - Grace, Jennifer R; Saina, Anna K; E, Maheswari; R, Srinivasa; Subeesh, Viswam (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The purpose of this study was to assess the incidence and pattern of adverse drug reactions (ADRs) reported from the department of neurology of a tertiary care hospital in Karnataka, India. Methods: It is a hospital-based prospective, observational study, conducted among the inpatients of all age groups of either sex for a period of 6 months. ADRs were reported by the clinical pharmacists and physicians of this hospital. ADRs obtained were categorized based on its causality, severity, preventability, predictability, and outcomes. Binary logistic regression was carried out to identify the predictors of ADR and Kaplan–Meier analysis was performed for survival analysis. Results: A total of 250 patients were enrolled for the study in which 108 (43%) patients were presented with at least one ADR and a total of 212 ADRs were observed. The highest rate of ADRs was observed with antiepileptics 61 (29.5%). The most commonly reported that ADRs were skin reactions 23 (10.8%). Causality was assessed using three different scales which showed that most of the ADRs were probable. Severity, preventability, and predictability were assessed, of which 125 (59%) ADRs were moderate, 192 (90.6%) ADRs were probably preventable, and 156 (73.6%) ADRs were predictable, respectively. The outcomes showed that 150 (70.1%) patients recovered from the reactions. Predictors such as polypharmacy and duration of stay were found to be significant. Conclusion: The study concluded that the prevalence of ADRs in the department of neurology is high. Thus, early detection and management of ADRs are essential to avoid further complications of the reaction.